2016
DOI: 10.1002/pbc.26271
|View full text |Cite
|
Sign up to set email alerts
|

No impact of disease and its treatment on bone mineral density in survivors of childhood acute lymphoblastic leukemia

Abstract: BMD Z-scores were similar among ALL survivors and controls. It was reassuring that there was no detrimental impact of the disease or its treatment on BMD. Future studies are required to determine the best possible ways to target the modifiable risk factors (diet, vitamin D) to optimize bone health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 49 publications
(126 reference statements)
2
27
0
Order By: Relevance
“…These studies confirmed some of the well‐documented issues in childhood cancer survivors including the previously reported detrimental effects of cranial radiation on neurocognition 10‐13 and neuroendocrine axis, 12 of neck radiation on thyroid function, 8,11 and of alkylating agents on fertility 11,13,25,26 . Contrary to published literature, 29 a single study from India showed that bone mineral density in leukemia survivors was similar to that of controls 23 . This may be explained by the relatively lower doses of methotrexate and steroids as well as that of cranial radiation used in their cohort.…”
Section: Scientific Knowledgesupporting
confidence: 83%
See 2 more Smart Citations
“…These studies confirmed some of the well‐documented issues in childhood cancer survivors including the previously reported detrimental effects of cranial radiation on neurocognition 10‐13 and neuroendocrine axis, 12 of neck radiation on thyroid function, 8,11 and of alkylating agents on fertility 11,13,25,26 . Contrary to published literature, 29 a single study from India showed that bone mineral density in leukemia survivors was similar to that of controls 23 . This may be explained by the relatively lower doses of methotrexate and steroids as well as that of cranial radiation used in their cohort.…”
Section: Scientific Knowledgesupporting
confidence: 83%
“…A summary of results of 21 studies 8‐28 is tabulated (Supporting Information Table 1) and categorized by organ systems and late effects as used in the Children's Oncology Group Survivorship Guidelines 29 . All except one 8 of these studies have been published in the last decade, highlighting the recent expansion in work in this area in India.…”
Section: Scientific Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…52 Also, our definition of low BMD is consistent with prior studies by others in survivors. 23,26,27,29,[31][32][33][34][35][36][37][38][39][40]53 An important consideration is the clinical implications of identifying reduced BMD. The COG long-term follow-up guidelines recommend survivors with/at risk of decreased BMD conduct regular weight-bearing activity and ensure adequate vitamin D/calcium intake through diet or supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…26,29,34,35 Low BMD was defined as >1 SD (z-score less than −1) and very low BMD as >2 SDs (z-score less than −2) below age-matched, sex-matched, and race-matched norms, consistent with prior studies in childhood cancer survivors. 13,[36][37][38][39][40]…”
Section: Bmd Evaluationmentioning
confidence: 99%